(untitled) (Research, Society and Development, 2021)
The use of teaching materials in genetics disciplines has become a practice with increasing demand due to the high efficiency it has provided in teaching and learning of microscopic subjects impossible to be seen with the naked eye. This technique produced dynamic and relaxed practical lessons, with greater understanding, learning and concentration, and the interest and collaboration among students during group work, and reduced the dispersion and use of cell phones in the classroom. In addition, according to the Unesp librarian, there was an increase in the search and use of books from the library by students when compared to last years. On the other hand, a factor that has increased the interest in the adoption of didactic materials by teachers is the low cost of production compared to the high cost of reagents and equipment used in traditional practical classes used in laboratories. Our aim is to present details of the construction of the DNA molecule using inexpensive didactic materials, the steps evolved in the creation and the forms of evaluation used by the author to achieve the presented results, and discuss its use in the higher education. This didactic model was developed at the beginning of the author’s academic career and used in the teaching of genetics, general biology and molecular biology disciplines in different courses over several years.